2014
DOI: 10.1161/strokeaha.114.006707
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Predictors of Stroke After Acute Myocardial Infarction

Abstract: Background and Purpose-Stroke is a serious complication after acute myocardial infarction (AMI) and is closely associated with decreased survival. This study aimed to investigate the frequency, characteristics, and factors associated with in-hospital and postdischarge stroke in patients with AMI. Methods-Eight thousand four hundred eighty-five consecutive patients admitted to a cardiology intensive care unit for AMI, between January 2001 and July 2010. Stroke/transient ischemic attack were collected during 1-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
2
23
0
5
Order By: Relevance
“…Hachet and colleagues reported that typical cases occurred during the first week and 33% during the first 24 hours [6]. These rates can be confirmed by the observational studies of American and Swedish patient registries which show the results of representative patient populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Hachet and colleagues reported that typical cases occurred during the first week and 33% during the first 24 hours [6]. These rates can be confirmed by the observational studies of American and Swedish patient registries which show the results of representative patient populations.…”
Section: Discussionmentioning
confidence: 78%
“…The Trial of ORG 10172 in Acute Stroke Treatment (TOAST trial) studied ischemic strokes during hospital stay at the acute phase of myocardial infarction: 60% was of cardioembolic origin and 36% were of undetermined pathogenesis [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, diabetes, dehydration, hypertension or instable blood-pressure, reduced renal function, reduced left ventricular ejection faction, newly detected atrial fibrillation and previous MI or stroke have been described as independent risk factors for IHS [16][17][18][19][20] . Although IHS patients generally have a higher vascular burden 3 , the dominant etiology of IHS is cardioembolism.…”
Section: Etiology Risk Factors and Outcomementioning
confidence: 99%
“…The high incidence of IHS on cardiological wards suggests that direct injury or interventional manipulation of the heart further enhances the risk of cardioembolism. The closer in time the index event, the higher the IHS risk: four out of five strokes after MI occur during the first five days 21 . The absolute periprocedural or -operative risk to suffer from IHS is about 0.25% in PCI 17 , 0.9% after acute coronary events 22 and about 1.4% after CABG 23 .…”
Section: Etiology Risk Factors and Outcomementioning
confidence: 99%
See 1 more Smart Citation